MARKET STRUCTURES, SHORT-TERM AND LONG-TERM MARKET DISTRIBUTION AND THEIR ECONOMIC EFFICIENCY (Web of Discoveries: Journal of Analysis and Inventions, 2024)
In this article, we study the dynamics of market structures and their impact on stabilization and long-term market dynamics, focusing on overall economic efficiency. We consider different market forms, such as perfect competition, monopoly, monopolistic competition, and oligopoly, and the structure under analysis that affects pricing, output, and overall welfare. We examine the efficiency implications of each structure, distinguished by productive, allocative, and dynamic efficiency. We then assess the role of entry and exit, technological innovation, and efficiency regulating factors in different market structures. By comparing short-term outcomes (such as immediate profit maximization and pricing strategy) with long-term outcomes (including stability, innovation, and equilibrium competition), we provide insight into how market structure exploits performance and trends over time.